A Clinical Study of Tikta Ksheer Sarpi Basti In Baldness and Hair Fall - Ranawat Rajendra Singh, Dr (International Journal of Pharmaceutical & Biological Archive, 2015)
A Clinical Study of Tikta Ksheer Sarpi Basti In Baldness and Hair Fall